A novel HDAC inhibitor chidamide combined with imatinib synergistically targets tyrosine kinase inhibitor resistant chronic myeloid leukemia cells - He, Bailin; Wang, Qiang; Liu, Xiaoli; Lu, Ziyuan; Han, Jiaochan; Pan, Chengyun; Carter, Bing Z.; Liu, Qifa; Xu, Na; Zhou, Hongsheng (Biomedicine & pharmacotherapy, 2020)
Chidamide is a novel selective histone deacetylase inhibitor (HDACi) with promising activity in hematological malignancies, but its role in chronic myeloid leukemia (CML) was marginally addressed. In this study, we firstly demonstrated that chidamide alone inhibited CML cells proliferation, induced apoptosis and cell cycle arrest. Further, chidamide combined with imatinib (IM) induced synergistic lethality in CML cell line KBM5, as well as IM-resistant CML cells KBM5T315I, associated with a marked reduction of Bcr-Abl kinase activity and acetyl-histone H3 expression. The combination treatment markedly inhibited constitutive activity of β-catenin signaling in IM-resistant cells and abolished the protective effects of mesenchymal stromal cells (MSCs) to CML cells. In addition, the co-treatment significantly reduced Bcr-Abl and β-catenin transcript levels and induced apoptosis of primary CD34+ stem/progenitor cells derived from blast crisis (BC)-CML patients, but exhibited minimal toxicity to normal CD34+ progenitors. Collectively, our data show that combination of chidamide and imatinib synergistically targets tyrosine kinase inhibitor (TKI) -resistant BC-CML cells via inhibition of Bcr-Abl and β-catenin signaling, suggesting that this combination has the potential for treating TKI-resistant CML and improving clinical outcomes of BC-CML patients.